2018
DOI: 10.1016/j.pharmthera.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone and the brain: Mechanisms of action in development and role in protection and promotion of recovery after brain injury

Abstract: Thyroid hormone (TH) is essential for normal brain development and may also promote recovery and neuronal regeneration after brain injury. TH acts predominantly through the nuclear receptors, TH receptor alpha (THRA) and beta (THRB). Additional factors that impact TH action in the brain include metabolism, activation of thyroxine (T4) to triiodothyronine (T3) by the enzyme 5'-deiodinase Type 2 (Dio2), inactivation by the enzyme 5-deiodinase Type 3 (Dio3) to reverse T3 (rT3), which occurs in glial cells, and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 116 publications
(152 reference statements)
0
50
0
1
Order By: Relevance
“…Although the function of MCT8 as a transporter of thyroid hormones is well known in other cells, the exact function of MCT8 in the physiological pHi homeostasis of cHCECs has yet to be elucidated. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Although the function of MCT8 as a transporter of thyroid hormones is well known in other cells, the exact function of MCT8 in the physiological pHi homeostasis of cHCECs has yet to be elucidated. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Thyroid derived hormones are iodinated signalling molecules that subserve evolutionarily ancient biologic functions (Crockford, 2009;Holzer et al, 2017;Taylor and Heyland, 2017), and TH plays roles in vertebrate neurodevelopment and brain disease (Bernal, 2005;Liu and Brent, 2018). Lack of TH in utero and in early life causes severe cognitive impairment, with extensive white matter pathology (Rosman, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…TBI is well known to cause changes in systemic TH levels 8 . Accumulating evidence from clinical and experimental studies has indicated that TH treatment showed neuroprotective properties after acute brain injury, including stroke and TBI [9][10][11] . Understanding TH's actions and the mechanisms regulating TH functions in the adult brain is essential to design potential therapeutic strategies for TBI, due to dysregulated TH signaling during this procession.…”
Section: Introductionmentioning
confidence: 99%